Nature and Instigation of Medication Errors and Gazed Barriers in Reporting Them - A Prospective Observational Study - Murali, Vimali; Thamisetty, Durgaprasad; Yalvarthi, Prasanna Raju (Indian Journal of Pharmacy Practice)
Introduction: The goal of drug therapy is the improvement of a patient’s health related quality of life while minimizing patient risk. But there are inherent risks associated with the therapeutic use of drugs and administration devices. Aim: Present study aims to identify and categorize MEs in the patients who were admitted in the General Medicine, Pediatrics and Surgery Departments in a tertiary care teaching hospital, Tirupati. The study also extended to find out the cause of MEs and the possible barriers for reporting the MEs. Methodology: A specially designed proforma was used for patient data collection & the study was approved by institutional ethics committee. Inclusion criteria includes, patients who were hospitalized for more than three days and who were willing to give informed consent to participate in the study. Results: The prescriptions of the 100 patients included in the study were analyzed for medication errors and 52.7% of prescriptions were presented with medication errors. The persons involved in the medication errors include physician (prescriber), nurse (administrator) and the patients (consumer). The major causes of MEs were found to be excessive work load, lack of knowledge and non-compliance by the patients to the drugs. Conclusion: The establishment of a blame-free, non-punitive environment can promote ME reporting.
Keywords: Medication Errors (ME); NCCMERP; HRQOL; Barriers of ME reporting; Clinical pharmacist; Patient care